Green synthesis of silver nanoparticles from Brownlowia tersa leaf extract: multifaceted evaluation of antibacterial, antioxidant, cytotoxic, and anti-alzheimer potential - Md Ridoy Hossain; Md Al Saber; Md. Anisul Hoque; Md. Shamsur Rahman; Florence Bornali Ratno; Md. Nazmul Hasan Zilani; Md. Ohiduzzaman; Md. Nazmul Hasan (PLoS ONE, 2025)
This study reports the first green synthesis of silver nanoparticles (AgNPs) using an aqueous leaf extract of Brownlowia tersa ( B. tersa ), confirming their formation via UV-Vis spectrophotometry with a peak at 472 nm. The AgNPs were evaluated for their antimicrobial and neuroprotective activities, particularly for Alzheimer’s disease. GC-MS and FT-IR analyses identified phenolics and flavonoids as the capping and reducing agents in the synthesis process. FESEM imaging showed nanoparticles of varied shapes and sizes, while EDX analysis confirmed the presence of silver, oxygen, and carbon. The antimicrobial activity was demonstrated with inhibition zones ranging from 8.5 to 10.5 mm against Staphylococcus aureus , Bacillus cereus , Shigella flexneri , and Pseudomonas aeruginosa at concentrations of 100 and 200 μg/disc, compared to control, deionised water. In antioxidant assays, AgNPs exhibited an IC₅₀ of 1533.448 μg/ml, significantly higher than L-ascorbic acid (IC₅₀: 83.948 μg/ml) and the plant extract (IC₅₀: 254.438 μg/ml), indicating weaker antioxidant properties of AgNPs. The cytotoxicity of the AgNPs was assessed using the brine shrimp lethality test, yielding LC₅₀ value of 13.50 μg/ml, indicating moderate toxicity. Neuropharmacological tests, except the elevated plus maze, on swiss albino mice revealed significant anxiolytic effects ( p < 0.05 ) and enhanced locomotor activity. Molecular docking studies of bioactive compounds from B. tersa leaves with Alzheimer’s and bacterial infection-related proteins revealed binding energies from −7.7 to −5.2 kcal/mol, with Benzamide, N-ethyl-N-[(4-ethylaminophenyl) sulfonyl]- and 3,4-Dihydroxyphenylglycol showing the strongest affinities. While the results are promising, the study acknowledges challenges in scaling up the synthesis process and emphasises the need for further research into the long-term biological effects and safety of AgNPs. Overall, B. tersa -derived AgNPs show great potential for therapeutic applications in bacterial infections and neurological disorders, but scalability and safety require more investigation.